A neutralizing antibody-inducing peptide of the V3 domain of feline immunodeficiency virus envelope glycoprotein does not induce protective immunity. - Lombardi, S (1994)
Specific-pathogen-free cats, immunized with a 22-amino-acid synthetic peptide designated V3.3 and derived from the third variable region of the envelope glycoprotein of the Petaluma isolate of feline immunodeficiency virus (FIV), developed high antibody titers to the V3.3 peptide and to purified virus, as assayed by enzyme-linked immunoassays, as well as neutralizing antibodies, as assayed by the inhibition of syncytium formation in Crandell feline kidney cells. V3.3-immunized animals and control cats were challenged with FIV and then monitored for 12 months; V3.3 immunization failed to prevent FIV infection, as shown by virus isolation, anti-whole virus and anti-p24 immunoglobulin G antibody responses, and positive PCRs for gag and env gene fragments. Sequence analysis of the V3 region showed no evidence for the emergence of escape mutants that might have contributed to the lack of protection. The sera of the V3.3-hyperimmunized cats and two anti-V3.3 monoclonal antibodies neutralized FIV infectivity for Crandell feline kidney cells at high antibody dilutions but paradoxically failed to completely neutralize FIV infectivity at low dilutions. Moreover, following FIV challenge, V3.3-immunized animals developed a faster and higher antiviral antibody response than control cats. This was probably due to enhanced virus replication, as also suggested by quantitative PCR data.